INSEMINASI BUATAN (IB) PADA TERNAK BABI DI PETERNAKAN CV. ADHI FARM, SOLO - , RUTH ELOK CYNTIARA; , Dr.drh. Surya Agus Prihatno,MP. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
CV pig farms. Adhi Farm is located in the hamlet Sepreh, Sroyo Village, District Cork, Karanganyar, Central Java perform the mating system of artificial insemination (AI) and natural mating system that aims to improve the genetic quality of livestock in a population until almost similar to its parent. Job Training (PKL) which took place on March 17 to 22 have performed at the farm aims to determine the implementation of IB in pigs, ranging from the preparation of males and females, semen collection, semen evaluation, and implementation of artificial insemination. The material used for collecting cement is 1 stud pig, and 8 females who performed the artificial insemination. Techniques for collecting data was obtained by the method of direct observation, interview, follow the activities and records obtained from sows. And from the results of the data acquisition is known that before artificial insemination is done, firstly we should prepare tools, prepare males, females , storage cement, and cement evaluation. Mating system is done on the farm is using the mating system of artificial insemination (AI). Mating the artificial insemination is usually performed on several parent groups weaned at the same time so that the lust time is the same. Before insemination, cement evaluating and polling are done. Polling conducted in special cages cement shelter with the help of a dummy (female pig artificial). The volume of cement at the shelter in once a polling is 250 ml and it is colorless (clear). Artificial insemination should be done at the right time in order to deliver results that pregnancy rate incr eased from first parity to fifth parity . So the detection lust should be known regularly and it is required a special schedule in detecting carnal lust prevent a missed period.